The Language of Returning Emigrant Children: Preliminary Insights - Bikelienė, Lina; Juknevičienė, Rita; Poderienė, Nida; Pribušauskaitė, Joana; Tamulionienė, Aurelija (Verbum, 2022)
The article overviews the Lithuanian language of returning emigrant children. It is based on the project “Linguistic Integration of Returning Emigrant Children: Proficiency in Lithuanian and its Development” (RCL Agreement No. S-REP-21-1), implemented in 2021–2022. The data were selected from two Lithuanian language children’s corpora (returning emigrant children (KG) and permanently residing in Lithuania children (KL)) collected during the project at eight Lithuanian schools. The corpora consist of the Lithuanian language production by children aged 8–12 who returned to Lithuania from English-speaking countries 1–2 years ago and by their peers in Lithuania. The article aims to identify differences in the linguistic expression of KG and KL by comparing the word frequency lists and overviewing verb, noun, and adjective. The quantitative findings show no significant differences in the use of the selected parts of speech. The results suggest that according to the available language skills and competences, the returning emigrant children can communicate on everyday topics quite freely, and their linguistic expression is similar to the language of their peers in Lithuania.